Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Get immediate and reliable solutions to your questions from a knowledgeable community of professionals on our platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Answer:
y=1, x=-4
Step-by-step explanation:
Solve by substitution. [tex](-16y=4x) = ( y=\frac{4x}{-16} )=(y=-\frac{x}{4} )[/tex]
[tex](4x +27y=11)=[4x+27(-\frac{x}{4} )=11][/tex]
Simplified[tex]\begin{bmatrix}-\frac{11x}{4}=11\end{bmatrix}[/tex]
Solved[tex]x=-4[/tex]
Substitute again[tex]-16y=4(-4)[/tex]
[tex]-16y=-16[/tex]
Solve[tex]y=1[/tex]
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.